Endoplasmic Reticulum Stress-Mediated Basolateral Amygdala GABAergic Neuron Injury Is Associated With Stress-Induced Mental Disorders in Rats - Wang, Songjun; Shi, Weibo; Zhang, Guozhong; Zhang, Xiaojing; Ma, Chunling; Zhao, Kai; Cong, Bin; Li, Yingmin (Frontiers in Cellular Neuroscience, 2019)
The amygdala is an important center of fear learning and memory and plays a critical role in regulating stress disorders. Previous studies have shown that changes in the amygdala caused by stress are an important cause of mental disorders including anxiety, but the specific mechanism remains unclear. Therefore, the purpose of this study was to investigate whether mental disorders induced by stress are related to γ-aminobutyric acid (GABA)ergic neuron damage in the basolateral amygdala (BLA) and whether endoplasmic reticulum stress (ERS) is involved in the injury process. Rat models of different durations of stress were established by restraint and forced ice-water swimming. Behavioral tests and high-performance liquid chromatography (HPLC) were used to detect anxiety in rats and changes in neurotransmitter levels in the BLA. Morphological approaches and microscopy-based multicolor tissue cytometry (MMTC) were used to detect the damage-induced changes in GABAergic neurons in the BLA. Immunofluorescence double labeling was used to detect the expression of ERS-related proteins before and after the inhibition of protein kinase R-like endoplasmic reticulum kinase (PERK) pathway. Stress resulted in damage to GABAergic neurons in the BLA, decreased GABA and increased glutamic acid (GLU) levels, perturbation of the excitation/inhibition (E/I) ratio in the BLA, and obvious anxiety disorders in rats. Moreover, ERS-mediated GABAergic neuron injury was an important cause of neurotransmitter level changes in the BLA. These results suggested that ERS-mediated GABAergic neuron injury in the BLA may be an important cause of stress-induced mental disorders.